MANAJEMEN INTEGRASI ZAKAT MAL DAN PEMBERDAYAAN KEARIFAN LOKAL PERELEK DALAM MENINGKATKAN KESEJAHTERAAN UMAT (Studi Kasus : Masjid Jami Al-Amin Desa Sukawening Kec. Ciwidey Kab. Bandung) - Eep Jamaludin; Hanafiah Hanafiah; Faiz Karim Fatkhullah (Penerbit Widina, Widina Media Utama, 2026)
Background: The management of Zakat Mal at the village mosque level is often trapped in a traditional paradigm characterized by the absence of formal institutions, lack of transparency, and short-term consumptive distribution patterns. This phenomenon contrasts sharply with the vitality of local wisdom, such as the